Compatible solutes from hyperthermophiles improve the quality of DNA microarrays - Evangelisti Rita; Liu Chang-Gong; Helmer Citterich Mauro; Arcelli Diego; Taccioli Cristian; Valentini Davide; Marchesini Jlenia; Rossi Simona; Liu Xiuping; Mascellani Nicoletta; Russo Giandomenico; Santos Jorge M; et al. (BMC Biotechnology, 2007)
Abstract Background DNA microarrays are among the most widely used technical platforms for DNA and RNA studies, and issues related to microarrays sensitivity and specificity are therefore of general importance in life sciences. Compatible solutes are derived from hyperthermophilic microorganisms and allow such microorganisms to survive in environmental and stressful conditions. Compatible solutes show stabilization effects towards biological macromolecules, including DNA. Results We report here that compatible solutes from hyperthermophiles increased the performance of the hybridization buffer for Affymetrix GeneChip® arrays. The experimental setup included independent hybridizations with constant RNA over a wide range of compatible solute concentrations. The dependence of array quality and compatible solute was assessed using specialized statistical tools provided by both the proprietary Affymetrix quality control system and the open source Bioconductor suite. Conclusion Low concentration (10 to 25 mM) of hydroxyectoine, potassium mannosylglycerate and potassium diglycerol phosphate in hybridization buffer positively affected hybridization parameters and enhanced microarrays outcome. This finding harbours a strong potential for the improvement of DNA microarray experiments.